INDONESIA KETUA ASEAN 2023 : MENILIK MANUSKRIP KEISLAMAN ASEAN MELALUI MANUSKRIP MARAWI - Hermawan, Eman; Limbong, Priscila Fitriasih; Buduroh, Mamlahatun (TARBAWI:Journal on Islamic Education, 2024)
ASEAN has three pillars of cooperation, namely the political and security pillar; economic pillar; and socio-cultural pillars. In the context of the socio-cultural pillar, the ASEAN region has an extraordinary diversity of manuscripts; has an extraordinary diversity of languages, scripts, culture and religious content. However, ASEAN also has its own challenges, such as conflict or extremism that could threaten the existence of manuscripts. One of the ASEAN regions that has armed conflict but has many Islamic manuscripts is Marawi, which has scientific relations with Indonesian ulama. The aim of this research is to see the transmission of knowledge from Marawi ulama in the Philippines with Indonesian ulama. The method used is a literature study approach. The research results show that the manuscripts in Marawi are connected to scholars in Indonesia. The research conclusion is the connection between Indonesia and the Philippines in the past, both scientific transmission and social, economic and religious interactions. Therefore, the Marawi catalog can be studied in more depth, both for academic purposes and for other studies.